IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH ROLE PLAYING MODELS FOR CLASS II STUDENTS SDN SUMOBITO 1 JOMBANG - Vera Vidyasari; Agung Setyawan (Citra Dharma Cindekia, 2022)
Mathematics is a field of study whose study is global so it is always available and needed in other fields of study as well as in the application of everyday life. Therefore, it is important for students to understand mathematics. The background of the problem in this research is the low mathematics learning outcomes of class II students at SDN Sumobito 1 Jombang. The purpose of this research is to improve students' mathematics learning outcomes through the application of role playing models. The required data were taken by using the methods of tests, interviews, observation, and documentation. The collected data was then analyzed using quantitative descriptive analysis techniques. The result of the research is that there is an increase in the number of students who complete before arriving after the action. Before the action, the percentage of students who completed the first cycle was 12.5% ??and after being given the action in the second cycle it became 93.75%. The average learning outcomes also increased from 46.25 initially, after the action in the second cycle to 84.37, this shows the role playing learning model can improve mathematics learning outcomes for second grade students at SDN Sumobito.